2018
DOI: 10.1007/s13300-018-0461-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sitagliptin in Hispanic/Latino Patients with Type 2 Diabetes: A Pooled Analysis from Ten Randomized, Placebo-Controlled Phase 3 Clinical Trials

Abstract: IntroductionTo assess the efficacy and safety profile of the dipeptidyl-peptidase-4 inhibitor sitagliptin in a population of self-identified Hispanic/Latino patients with type 2 diabetes.MethodsData were pooled from ten randomized, double-blind studies in which subjects were treated with sitagliptin 100 mg/day (as mono- or combination therapy) or placebo, and used to evaluate the glycemic efficacy, safety, and tolerability of sitagliptin compared with placebo after 24 weeks of treatment.ResultsA total of 804 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Expanding on the role of glucose, DPPIV inhibitors such as sitagliptin are effective against T2DM [11][12][13]15 . Sitagliptin improved glycemic control in randomized controlled clinical trials involving adults with T2DM, indicated by a 20% reduction in hemoglobin A1C [22][23][24][25][26][27] ; this protective effect has been attributed to decreased degradation of the incretin hormones GLP-1 and GIP, both of which potentiate glycemic control after a meal and promote satiety, acting over time to improve metabolic function 62 . However, the effects of sitagliptin on weight control remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expanding on the role of glucose, DPPIV inhibitors such as sitagliptin are effective against T2DM [11][12][13]15 . Sitagliptin improved glycemic control in randomized controlled clinical trials involving adults with T2DM, indicated by a 20% reduction in hemoglobin A1C [22][23][24][25][26][27] ; this protective effect has been attributed to decreased degradation of the incretin hormones GLP-1 and GIP, both of which potentiate glycemic control after a meal and promote satiety, acting over time to improve metabolic function 62 . However, the effects of sitagliptin on weight control remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, greater plasma DPPIV activity is observed in models of genetic obesity (ob/ob) and diet-induced obesity (DIO) 20 ; meanwhile, mice that lack one or both Dpp4 alleles in adipocytes and/or hepatocytes exhibit reduced plasma DPPIV activity and are protected from DIO 21 . DPPIV has also been extensively studied in the context of T2DM and insulin signaling, and DPPIV inhibitors such as sitagliptin are effective, United States Food and Drug Administration (FDA)-approved second-line treatments for T2DM [22][23][24][25][26][27] . In line with the hypothesis that DPPIV is an active player in obesity progression, results from clinical trials indicate that DPPIV inhibitors can improve weight control [28][29][30][31][32][33][34] , systemic metabolism [22][23][24][25][26][27] , and inflammatory responses [35][36][37][38][39][40][41][42][43] all critical processes that become progressively dysregulated in the context of obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of the abovementioned studies indicated that sitagliptin has no effect on improving liver fibrosis. Additionally, most of the included studies demonstrated no improvement in hepatic content, possibly because sitagliptin has only slight effects on weight loss [59,61].…”
Section: Discussionmentioning
confidence: 99%